Analisis Store Atmosphere, Keragaman Produk, Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen (Studi Kasus Halalan Mart Sukorejo, Kabupaten Pasuruan) - Edi Saputra; Rois Arifin; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of research is to analyze the effect of store atmosphere, product diversity, and service quality on consumer buying interest at Halalan Mart Sukorejo. The population in this study are consumers of Halalan Mart. The sampling technique used purposive sampling with a sample size of 90 respondents to Halalan Mart consumers. The method used in processing data using a quantitative approach with multiple linear regression analysis tools through the IBM SPSS 25 application program (statistical product and service solutions). From data management, it is found that store atmosphere and product diversity have a positive and significant effect on consumer purchase interest, while service quality does not, and simultaneously the three independent variables have a significant effect on consumer purchase interest. Keywords: Analysis Store Atmosphere, Product Diversity, Service Quality, Purchase Interest